In-plane trapping and manipulation of ZnO nanowires by a hybrid plasmonic field. Issue 18 (27th April 2016) - Zhang, Lichao; Dou, Xiujie; Min, Changjun; Zhang, Yuquan; Du, Luping; Xie, Zhenwei; Shen, Junfeng; Zeng, Yujia; Yuan, Xiaocong
Abstract : In this work, we achieve the in-plane trapping and manipulation of a single ZnO nanowire by a hybrid plasmonic tweezer system on a flat metal surface. Abstract : In general, when a semiconductor nanowire is trapped by conventional laser beam tweezers, it tends to be aligned with the trapping beam axis rather than confined in the horizontal plane, and this limits the application of these nanowires in many in-plane nanoscale optoelectronic devices. In this work, we achieve the in-plane trapping and manipulation of a single ZnO nanowire by a hybrid plasmonic tweezer system on a flat metal surface. The gap between the nanowire and the metallic substrate leads to an enhanced gradient force caused by deep subwavelength optical energy confinement. As a result, the nanowire can be securely trapped in-plane at the center of the excited surface plasmon polariton field, and can also be dynamically moved and rotated by varying the position and polarization direction of the incident laser beam, which cannot be performed using conventional optical tweezers. The theoretical results show that the focused plasmonic field induces a strong in-plane trapping force and a high rotational torque on the nanowire, while the focused optical field produces a vertical trapping force to produce the upright alignment of the nanowire; this is in good agreement with the experimental results. Finally, some typical ZnO nanowire structures are built based on this technique, which thus further confirms the potential of this method for precise manipulation of components during the production of nanoelectronic and nanophotonic devices.